DIAGNÓSTICO DOS ESTÁGIOS SUPERVISIONADOS DO CCENS/UFES:UM ESTUDO DE CASO - Almeida, Lidianne Bicalho (2020)
Supervised internship is a very important moment for undergraduate students, since it is their first contact with professional from the area, enabling cooperation between theoretical and practical knowledge. Allied to this, Law nº11.788/2008 started to r